Abuse in Childhood and Cardiometabolic Health in Early Adulthood: Evidence From the Avon Longitudinal Study of Parents and Children - Ana Goncalves Soares; Annie Zimmerman; Stan Zammit; Anke Karl; Sarah L. Halligan; Abigail Fraser (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Although childhood abuse has been consistently associated with cardiovascular disease in later adulthood, its associations with cardiometabolic health in younger adults are poorly understood. We assessed associations between childhood physical, sexual, and psychological abuse and cardiometabolic outcomes at 18 and 25 years. Methods and Results We used data on 3223 participants of the ALSPAC (Avon Longitudinal Study of Parents and Children). Exposure to childhood abuse was self‐reported retrospectively at 22 years. We used linear regression to assess the associations between childhood abuse and cardiometabolic outcomes at 18 and 25 years. At 18 years, physical (β 1.35 kg/m2; 95% CI, 0.66–2.05), sexual (β 0.57 kg/m2; 95% CI 0.04–1.11), and psychological (β 0.47 kg/m2; 95% CI 0.01–0.92) abuse were associated with higher body mass index. Physical abuse was also associated with lower high‐density lipoprotein cholesterol (β −0.07 mmol/L; 95% CI, −0.13 to −0.01) and higher C‐reactive protein (31%; 95% CI, 1%–69%), and sexual abuse was associated with higher heart rate (β 1.92 bpm; 95% CI 0.26–3.58). At age 25, all 3 types of abuse were additionally associated with higher insulin, and sexual abuse was associated with lower cholesterol (−0.14 mmol/L; 95% CI, −0.26 to −0.01). The age at which abuse occurred (<11or 11–17 years) had little influence on the associations, and when sex differences were evident, associations were stronger in men. Conclusions Childhood abuse is associated with negative cardiometabolic outcomes even by young adulthood. Further follow‐up will determine whether associations strengthen across the life course and whether sex differences persist, which is essential for targeting effective screening programs and early interventions in those who suffered abuse in childhood.